The Comparison of Cooperative Learning Methods Make a Match Type with Scrable Types Students' Learning Results for 8th Grade in Government Junior High School 2 Kualuh Selatan - Azhar, Khairul; Saragih, Siti Zahara; Hasibuan, Lily Rohanita; Rahma, Indah Fitria; Nazliah, Rahmi (Budapest International Research and Critics University, 2021)
This study aims to determine the comparison of student learning outcomes in the application of the Make a match learning method with the Scramble method on the subject matter of the Excretory System. The research design used was a quasi-experimental group design with a pretest-posttest experimental group design. In the experimental class I which was taught using the Make a match method the average score of student learning outcomes was 63.56 and the increase in the average score of student learning outcomes was 90.04. In the experimental 2th grade, which was taught using the Scramble method, the average score of student learning outcomes was 50.92 and the increase in the average score was 94.60. The results showed that there were differences in student learning outcomes between the experimental 1th grade and the experimental 2th grade.